Uniwersytet jako przestrzeń życia w ideach = University as a space for living among ideas - Murawska, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author takes the changes in expectations towards universities as a starting point for the article. She indicates the dominance of such expectations as: effectiveness, competitiveness, marketization, and their consequence - measurability. Referring to Gadamer`s diagnose of the crisis of universities, the author regards the lack of living among ideas to be its cause. Concern for the development of ideas (and not for quick, abundant and cheap action) might be a way of overcoming this crisis.
Keywords: oczekiwania wobec uniwersytetu; mierzalność pracy naukowej; sens pracy naukowej; expectations towards universities; measurement of scientific output; concern for ideas